Description of Management of Hair Beauty Training Program (Junior Stylist) at UPT BLK Lubuk Sikaping - winda safitri; Solfema Solfema (Universitas Negeri Padang, 2023)
The motive of this research was the success of Hairstyle Traineeship ( Yunior Stylist ) which were marks by the succeeded of the trainees getting into workforce environment and their ability to open their own Hairstyle Shop. The success suspected to be not only by an excellent way of managing the hairstyle and beauty traineeship ( Yunior Stylist ) at the UPT BLK Lubuk Sikaping however it is observed from the aspects of planning, realisation, evaluation and implementation of the traineeship. This research is a Qualitative descriptive research that generates Data that describes the Who, What and where of an events or experiences from a subjective perspective. The subject in the research are the program manager ( trainer ) and the trainee of the Hairstyle traineeship ( Yunior Hairstyle ) ar the UPT BLK Lubuk Sikaping. The technique utilised in the collection of Data was Data Saturation which consisted of 5 Training Program Manager and 16 of trainees. Data collection technique utilised within the research was questionare, however the data collection tool used in the research was based on a statement with a simple yes/no questionare. As for data analysis technique used is percentage formula. The outcome of the research are showed that: 1) The traineeship planning program was appropriately to what the trainee needs, 2) The knowledge and skills were given to the trainee are accordingly to what they needs, 3) The trainee are able to understand the theory and and practical based on the purpose of the traineeship, 4) The trainee are able to implement the technique of hairstyling ( Yunior Stylist ).